Exploring how moral intelligence influences the enhancement of psychological resilience among Saudi university students: A case study at King Faisal university - Aldawsari, Hussam K. (International Journal of Innovative Research and Scientific Studies, 2025)
Student success in academic and social challenges depends on their possession of moral intelligence together with psychological resilience. The research reveals that moral intelligence plays a fundamental role in building psychological resilience for students attending King Faisal University in Saudi Arabia. The researchers measured moral intelligence through two scales on 386 students at King Faisal University, along with psychological resilience and its 4 axes. Moral intelligence scores for the research sample were found to be average based on measurements, while participants displayed stronger performance in conscientiousness and tolerance but weaker aspects in respect. Psychological resilience levels were moderate, while religious values received superior results, but social support proved quite weak. Females outperformed males in justice measures, although males demonstrated greater competence when it came to social abilities. The research findings establish that psychological resilience tightly matches with moral intelligence levels because religious commitment along with spiritual beliefs boost stress management abilities. Interventions need specific strategies in order to support respect for development and social support enhancement. Further research must analyze how these effects maintain their durability and should focus on various population groups in multiple settings. Studies based on this research will help scholars analyze moral intelligence development through different academic levels while demonstrating culture and subject-specific analysis.